PERANAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN PENDIDIKAN KARAKTER DI SD ISLAM TERPADU DARUSSALAM PALEMBANG - Zaleha, Indah Suci; Rosani, Meilia; Indrawat, Sri Wahyu (STKIP Pesisir Selatan, 2025)
This study aims to identify the strategies implemented by the principal in integrating character education into the curriculum, as well as the support and obstacles faced. The research method used is qualitative with a descriptive approach. Through this qualitative approach, data sources were obtained from observations, interviews with the principal, vice principal, teachers, and students of the Integrated Islamic Elementary School Darussalam Palembang. The determination of data sources in this study utilizes primary and secondary data. Based on the research results, it shows that the principal has played a key role in implementing character values, such as religiosity, discipline, and responsibility, through two methods: involving all school members, including the vice principal, subject teachers, and administrative staff, and collaborating with parents through the school committee. Although there are obstacles, consisting of two internal factors and external factors, the internal factors arise from the students themselves, who still find it difficult to accept character education values due to unfamiliarity. The second external factor comes from the environment, particularly the differences in students' family backgrounds. Therefore, collaboration between the school and parents is crucial for realizing effective character education.